STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DI SMA NEGERI 2 MALANG - Ahmad Muzaqi; Muhammad Hanif; Imam Safi’i (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
In the era globalization which is happening at this time the0development of science and0technology0also plays an important role for students. Because in that case both must run in balance. Therefore the goverment agreed0to improve a policy which is to0improve the0quality0of0education. The achievement0of the0results0of0the quality0of0education is a step that must be done by a teacher with the results of the quality of education is astep that0must be0done0by a teacher with the results of the efforts of professional abilities possessed by the teacher. Like wise0with0islamic0religious0education0teachers have a very important role, which the teacher as a facilitator in the process of learning activities. Therefore, as a teacher must provide motivation to students because motivation is one of the factors that can affect the spirit of the students degrees. Motivation0is0needed0by0every0student0to increase enthusiasm for learning. Thus a teacher is expected to provide motivation to students. Keywords:Learning0strategies, motivation0to0learning